Effective Method for Determining Environmental Loads on Supporting Structures for Offshore Wind Turbines - Dymarski Paweł; Ciba Ewelina; Marcinkowski Tomasz (Polish Maritime Research, 2016)
This paper presents a description of an effective method for determining loads due to waves and current acting on the supporting structures of the offshore wind turbines. This method is dedicated to the structures consisting of the cylindrical or conical elements as well as (truncates) pyramids of polygon with a large number of sides (8 or more). The presented computational method is based on the Morison equation, which was originally developed only for cylindrically shaped structures. The new algorithm shown here uses the coefficients of inertia and drag forces that were calculated for non-cylindrical shapes. The analysed structure consists of segments which are truncated pyramids on the basis of a hex decagon. The inertia coefficients, CM, and drag coefficients, CD, were determined using RANSE-CFD calculations. The CFD simulations were performed for a specific range of variation of the period, and for a certain range of amplitudes of the velocity. In addition, the analysis of influence of the surface roughness on the inertia and drag coefficients was performed. In the next step, the computations of sea wave, current and wind load on supporting structure for the fifty-year storm were carried out. The simulations were performed in the time domain and as a result the function of forces distribution along the construction elements was obtained. The most unfavourable distribution of forces will be used, to analyse the strength of the structure, as the design load.